Efficacy of a Digital Sports Vision Training Program for Improving Visual Abilities in Collegiate Baseball and Softball Athletes. Issue 7 (July 2021) - Shekar, Sandhya Uma; Erickson, Graham B.; Horn, Fraser; Hayes, John R.; Cooper, Scott
Abstract : SIGNIFICANCE: Dynamic reactive sports involve visual abilities such as visual acuity, depth perception, contrast sensitivity, and visual-motor reaction speed. This randomized, double-blinded control design showed no significant improvement in the visual parameters among athletes after training on a digital sports vision training program. PURPOSE: There is a need for evidence supporting the efficacy of recently developed digital training programs. METHODS: Thirty-two athletes from National Collegiate Athletic Association Division III softball and baseball teams were randomly divided into experimental and placebo training groups, undergoing three 20-minute training sessions per week for 3 weeks. The experimental group trained on procedures designed to improve dynamic visual acuity and depth perception, and the placebo group trained on procedures designed to have no direct impact on those same parameters. All measures were recorded at baseline, post-training, and after a month of no training. The athletes also completed a questionnaire to determine the efficacy of the placebo effect. RESULTS: There was no significant effect of evaluation type (post-training and follow-up) and condition (experimental and placebo) on any of the visual parameters. However, stereoacuity, contrast sensitivity, depth perception, and dynamic visual acuity showed minimum effect sizes of 0.5. Fifteen of 16 athletes in the placebo group thought they trained on experimental procedures. CONCLUSIONS: No significant improvement differences were seen between experimental and placebo training groups. However, stereoacuity, contrast sensitivity, and depth perception achieved minimum clinical relevance.